The 30-year wait for treatment of an acutely painful knee. (29th September 2014) - Davenport, Dominic; Colaco, Henry B; Edwards, Max R
Abstract : A 63-year-old retired man presented to our clinic reporting a severely painful, localised knee pain present for around 30 years and associated with a spontaneous palpable lump. He was prompted to seek medical advice at this point because his symptoms were exacerbated when his young grandchildren bumped into the knee. While radiographs were unhelpful, ultrasonography revealed a well-defined, subcutaneous soft tissue mass at the anterior aspect of the knee. Surgical excision was performed as a day case. Histological examination of the mass showed a glomus tumour. This patient had suffered for many years as a result of this painful mass but full resolution of his pain occurred immediately after excision.